Analisis Faktor-Faktor yang Mempengaruhi Pemilihan Tabungan Syariah pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Jambi - Ary Dean Amri; Anitha Octaviani; Adinda Putri Agustina; Noviya Rita; Nurita Nurita; Syahrul Gunawan (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this research is to determine which factors are more influential in influencing the choice of Syariah Bank savings (Y) among students at FEB Jambi University   ‘s. These Factors are classified as internal and external.This research applied quantitative research methods. The primary data sources are questionnaires that have been tested for validity and reliability as well as secondary data from various print and electronic media related to this research. SPSS 25.0 was used to analyze data using simple regression tests and multiple regression test. A random sampling method was used to choose 233 FEB students from Jambi University’s class of 2019-2022. Based on the results of the T test and F test, the internal factor variabel (X1) and external factor variabel (X2) obtained a significance value of 0.000 < 0.05, so it can be concluded that the internal factor variabel (X1) and external factor variabel (X2) affect the choice Syariah Bank savings (Y) for Jambi Universitas FEB students. Furthermore, based on the coefficient of determination (R2) results, the internal factor variabel (X1) has a value of 74.3% while the external factor variabel (X2) has a value of 49.9% . Thus, internal factor (X1), Which include personal, psychological, and economic factors, outweigh external factors (X2), which include cultural, social, and marketing factors, in influencing FEB Jambi University students’ choice of  Syariah Bank Savings (Y). Because of that, it is important for Syariah Bank side to improve both variabel in order to increase interest of syariah Bank in Indonesia.